Skrining Tekanan Darah Pada Lansia dengan Faktor Terkait di RT 03 dan RT 05, RW 01 Margosari, Kelurahan Salatiga, Kota Salatiga - Priska Grace Harefa; Kezia Damaria Momongan; Christy, Diva Sella; Dita Veronica Aula; Ersadita Adhisti (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2024)
Hypertension is a condition of blood pressure that is above the normal range, which is above 120 mmHg for systolic and 80 mmHg for diastolic. Hypertension problems are commonly found in the elderly (elderly) group and are a risk factor for various health problems. Aging that occurs in the elderly produces various changes in the function and structure of arterial blood vessels, increasing the risk of hypertension. Therefore, a study was conducted to determine the appropriate solution as a form of prevention of hypertension. This assessment activity was carried out through screening to people's homes in RT 03 and RT 05, RW 01 Margosari, Salatiga Village, Salatiga City. Most of the respondents had hypertension, which was as many as 8 people (57%). Meanwhile, there were about 6 people (42%) who did not experience hypertension. Lifestyle modification in accordance with balanced nutrition guidelines is a solution for the elderly to overcome hypertension problems. The purpose of this study was to determine the relationship between the lifestyle of the elderly with hypertension and find appropriate solutions as a form of intervention against hypertension in the elderly.